2006
DOI: 10.1186/1471-2334-6-163
|View full text |Cite
|
Sign up to set email alerts
|

Serologic indices of hepatitis B virus infection in military recruits in Greece (2004–2005)

Abstract: BackgroundThe prevalence of hepatitis B virus infection in Greece has been decreasing over the last decades. However, recent epidemiological data are lacking.MethodsWe studied 1,840 Army recruits from 05/2004 until 10/2005, and performed serological testing for HBsAg, anti-HBsAg, and anti-HBcAg. We also examined their association with several factors, including age, residential area, socioeconomic class, and educational level.ResultsMean age (± SD) of the recruits was 20.5 (± 2.1) years. Antibodies to HBV core… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
2
2

Year Published

2008
2008
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 12 publications
1
14
2
2
Order By: Relevance
“…This rate, although lower, is similar to the rate in Greece (62.2%) in 17-to 34-year-olds (German et al, 2006) and higher than the rate in the USA (31.5%) in 18-to 35-year-olds (Scott et al, 2005); both studies utilized military recruits and took place 10 years after mandatory hepatitis B immunization was established. As previously mentioned, anti-HBs titers may have decreased over the years, thus suggesting that many more than 40.7% of the subjects may be immunized.…”
Section: Discussionsupporting
confidence: 56%
“…This rate, although lower, is similar to the rate in Greece (62.2%) in 17-to 34-year-olds (German et al, 2006) and higher than the rate in the USA (31.5%) in 18-to 35-year-olds (Scott et al, 2005); both studies utilized military recruits and took place 10 years after mandatory hepatitis B immunization was established. As previously mentioned, anti-HBs titers may have decreased over the years, thus suggesting that many more than 40.7% of the subjects may be immunized.…”
Section: Discussionsupporting
confidence: 56%
“…Ces résultats témoignent de l'endémicité de cette affection en Côte-d'Ivoire et du caractère à risque que constitue la profession de sapeurs-pompiers. Dans les populations militaires en Occident [11,12,14,15], la préva-lence de l'antigène HBs était faible, variant de 0 à 6,6 %, corrélée à la faible endémicité de ce virus dans ces régions. Tous les patients porteurs de l'antigène HBs étaient anticorps anti-HBe positif et antigène HBe négatif.…”
Section: Discussionunclassified
“…Recently, a small survey on adolescents 15-19 years old showed a 78.4% complete coverage against hepatitis B [19]. A serosurvey among army recruits performed in 1997 found that only 1.3% had detectable anti-HBs antibodies indicating the low vaccine coverage among young adults [20], whereas a recent survey (2004)(2005) found that 62.17% of army recruits had postvaccine immunity [21], supporting the effectiveness of the ongoing immunization program. In Greece, we still have to make an effort to increase hepatitis B vaccination coverage since other countries report significantly higher coverage rates and WHO reports that in Europe the vaccine coverage is 76% [22].…”
Section: Discussionmentioning
confidence: 96%